Reconstructing Islamic Religious Education Curriculum through Qur’anic Values and Epistemology - Ahmad Nazar Fakhury; Nina Amelia; Fenia Marliana; Sri Wahyuni; Azrul Firmansyah Zulvan; Sinta Bella; Hafid Muslih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Contemporary Islamic Religious Education (PAI) curricula often suffer from fragmentation and technocratic reductionism that separate knowledge from values and moral responsibility. This study addresses the need for a more coherent curriculum framework by examining the Qur’an not merely as a normative source, but as an architectural foundation for curriculum design. The purpose of this study is to reconstruct the PAI curriculum based on thematic Qur’anic exegesis by articulating Qur’anic values and epistemology as organizing principles of educational aims, pedagogy, and assessment. Employing qualitative library research, the study applies thematic exegesis (al-tafsīr al-maudūʿī) to Qur’anic verses related to education, knowledge, and human responsibility, complemented by critical curriculum theory analysis. The findings reveal that Qur’anic values tauhīd, akhlāq or adab, ʿilm, and social responsibility function as an integrated curriculum architecture rather than isolated content areas. Moreover, Qur’anic epistemology conceptualizes knowledge as an amānah acquired through reflective and dialogical processes and validated through ethical praxis. These findings demonstrate that Qur’an-based curriculum reconstruction is an epistemological and pedagogical endeavor capable of producing a coherent, value-oriented, and contextually relevant PAI curriculum.